2013
DOI: 10.1002/pen.23616
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and structure of nylon‐6 crystallized in epoxy resin matrix

Abstract: Nylon-6/epoxy resin composite with multiphase morphology has been successfully prepared via polymerization of caprolactam in N-methylpyrrolidone using N-acetyl caprolactam as the initiator. This was followed by reactive blending of appropriate amount of the plastic with epoxy resin. The structure of nylon-6 prepared by solution polymerization is predominantly a [200, 020] a crystalline form with c [002] c crystalline form as the minor phase. Subsequently, nylon-6/epoxy composite was prepared at 150 C in a Tefl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…It is essential to understand the morphological evolution, because resultant morphology is the deciding factor behind physical and mechanical properties of polymer composites. The epoxy/nylon blends without clay have been reported before by our group . It was observed that as the epoxy/nylon blend is subjected to curing, nylon tends to crystallize in form of spherulites along with branching, growing radially outwards to occupy the free volume by using epoxy surface as heterogeneous template to grow upon.…”
Section: Resultssupporting
confidence: 55%
See 4 more Smart Citations
“…It is essential to understand the morphological evolution, because resultant morphology is the deciding factor behind physical and mechanical properties of polymer composites. The epoxy/nylon blends without clay have been reported before by our group . It was observed that as the epoxy/nylon blend is subjected to curing, nylon tends to crystallize in form of spherulites along with branching, growing radially outwards to occupy the free volume by using epoxy surface as heterogeneous template to grow upon.…”
Section: Resultssupporting
confidence: 55%
“…The melting trend of nylon‐6 in epoxy matrix followed the same fashion as in absence of epoxy. Presence of multiple peaks in nylon‐6/epoxy composite without clay suggests that nylon‐6 crystals used epoxy surface as a template to grow upon but the composites containing clay showed a single peak suggesting, nylon‐6 crystals preferred to use nano‐clay particles as nucleating agent over epoxy surface.…”
Section: Resultsmentioning
confidence: 54%
See 3 more Smart Citations